1995
DOI: 10.1055/s-2007-1015844
|View full text |Cite
|
Sign up to set email alerts
|

Funktionsbedingte Flächenänderungen des oro-pharyngo-laryngealen Vokaltraktes bei Sängern in der Magnetresonanztomographie

Abstract: The oro-pharyngeal-laryngeal resonating spaces were studied in 12 singers at varying stages of their training by means of medio-sagittal MRI images, and the results were compared. The singers were requested to sing /a/ /u/ and /i/ at various pitches and with increasing loudness. The total oro-pharyngo-laryngeal areas were integrated by means of the MRI sections. The relationship between the oro-pharyngeal and pharyngo-laryngeal areas was determined, as well as their ratio to total area. With increasing volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Inzwischen sind neue bild gebende Verfahren wie beispielsweise die Kernspintomographie verfügbar, um Unter suchungen bei Artikulation [9][10][11] und beim Singen bestimmter Laute durchzuführen. Auf diese Weise lassen sich Kehlkopf, Artikulatoren und Resonanzräume in geeigneten Schnitt ebenen darstellen [12][13][14],…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Inzwischen sind neue bild gebende Verfahren wie beispielsweise die Kernspintomographie verfügbar, um Unter suchungen bei Artikulation [9][10][11] und beim Singen bestimmter Laute durchzuführen. Auf diese Weise lassen sich Kehlkopf, Artikulatoren und Resonanzräume in geeigneten Schnitt ebenen darstellen [12][13][14],…”
Section: Introductionunclassified
“…Dabei wurden lautstärkeabhängi ge Flächenänderungen des Ansatzrohres in mediosagittalen Kernspintomogrammen be schrieben [14], Ziel dieses Beitrags ist es, Ver tikalstellungen des Kehlkopfes beim Singen in unterschiedlicher Tonhöhe und Lautstärke mit dem Verfahren der Kernspintomographie zu untersuchen. Die Untersuchungen wurden für die Vokale /a/.…”
Section: Introductionunclassified
“…In their early MRI studies, Neuschäfer-Rube et al [ 46 ] were not able to observe great differences concerning the vertical laryngeal position in relation to different loudness conditions. However, the same research group found changes in the oro-pharyngeal part of the vocal tract [ 47 ]. Since the MRI noise was not cancelled in these early studies and the perceptual term loudness was not objectified by means of SPL evaluations, the accuracy of the task performed by the subjects could not be verified.…”
Section: Introductionmentioning
confidence: 99%
“…Dabei wurden 3 Vokale untersucht, die in etwa gleicher Lautstärke und Tonhöhe artikuliert wurden. Angerstein et al beschäftigten sich in einer Studie mit der Darstellbarkeit des oro-pharyngo-laryngealen Vokaltraktes [2], und eine Arbeitsgruppe um Wein et al analysierte mittels der Magnetresonanztomographie (MRT) die Weitenänderung des Ansatzrohres beim Singen verschiedener Vokale mit zunehmender Lautstärke [3]. Wein et al untersuchten mittels MRT-Aufnahmen auch die Lautbildung und die Stellung von Gaumen und Zunge bei der Artikulation [4,5].…”
Section: Introductionunclassified